2019
DOI: 10.1111/nph.16100
|View full text |Cite
|
Sign up to set email alerts
|

Increase in lysophosphatidate acyltransferase activity in oilseed rape (Brassica napus) increases seed triacylglycerol content despite its low intrinsic flux control coefficient

Abstract: Summary Lysophosphatidate acyltransferase (LPAAT) catalyses the second step of the Kennedy pathway for triacylglycerol (TAG) synthesis. In this study we expressed Trapaeolum majus LPAAT in Brassica napus (B. napus) cv 12075 to evaluate the effects on lipid synthesis and estimate the flux control coefficient for LPAAT. We estimated the flux control coefficient of LPAAT in a whole plant context by deriving a relationship between it and overall lipid accumulation, given that this process is a exponential. Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 59 publications
3
18
0
Order By: Relevance
“…The increase in TAG content caused by the production of HaLPCAT1 or HaLPCAT3, in the absence of CsFAD2 expression, might be associated with increased acylation of LPA due to the LPAAT activity of these HaLPCATs. These results support the hypothesis that increasing the production of acyltransferases in yeast leads to a greater flux of intermediates and results in enhanced TAG accumulation, as described in plants (Zou et al, 1997;Woodfield et al, 2019). Indeed, yeast expressing HaLPCAT1 or HaLPCAT3 grew faster than yeast expressing HaLPCAT2 in the LPAAT activity assessment assays (Figure 4).…”
Section: Impact Of Recombinant Halpcat Production On Yeast Lipid Compsupporting
confidence: 87%
“…The increase in TAG content caused by the production of HaLPCAT1 or HaLPCAT3, in the absence of CsFAD2 expression, might be associated with increased acylation of LPA due to the LPAAT activity of these HaLPCATs. These results support the hypothesis that increasing the production of acyltransferases in yeast leads to a greater flux of intermediates and results in enhanced TAG accumulation, as described in plants (Zou et al, 1997;Woodfield et al, 2019). Indeed, yeast expressing HaLPCAT1 or HaLPCAT3 grew faster than yeast expressing HaLPCAT2 in the LPAAT activity assessment assays (Figure 4).…”
Section: Impact Of Recombinant Halpcat Production On Yeast Lipid Compsupporting
confidence: 87%
“…In contrast to GPAT-OE lines, overexpression of the second Kennedy pathway enzyme, LPAT, caused an increase in seed TAG despite its low intrinsic flux control coefficient 24 . Moreover, we show here that LPAT overexpression changed the cellular distribution of PC and TAG molecular species.…”
Section: Discussionmentioning
confidence: 81%
“…The resultant final plasmid was verified by restriction mapping and sequencing the insert. The construct used to produce LPAT/LPAAT ( TmLPAT2 ) overexpressing lines of B. napus has been described previously 24 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we have been interested in whether any other enzymes in the Kennedy pathway, apart from DGAT, could contribute significantly to the carbon flux into TAG formation. When we looked at lysophosphatidic acid acyltransferase (LPAAT), we found that its overexpression could raise TAG accumulation significantly and our collaborator, David Fell, was able to derive some new (and potentially very useful) equations to allow calculation of flux without using inhibitors to modify the radiolabeling of intermediates (Woodfield et al, 2019). Randy spotted our new publication and e‐mailed me, even before he had received his special “New Phytologist” copy that we had recommended!…”
Section: Working Togethermentioning
confidence: 99%